Pengaruh Kenaikan Cukai Rokok Tembakau Dan Penghasilan Terhadap Perilaku Merokok Di Malang - Chusna, Alfina Auliyaul; Saputri, Alyah Hasnah; Fadhila, Farah; Pardosi, Hilda Tamara; Putri W, Regina Nadia; Anggraini, Zahra Ayu (Universitas Katolik Soegijapranata, Semarang, 2025)
The government has decided to increase cigarette excise rates by 10% as of January 2024. This decision is inseparable from the aim of reducing the level of cigarette consumption in Indonesia. The purpose of this study was to determine the effect of increasing cigarette excise and income on smoking behavior. This study involved 104 respondents from the Malang Regency and City community who consumed cigarettes to fill out a questionnaire that was distributed directly or indirectly. The data analysis technique in the form of the McNemar test aims to determine the effect of increasing cigarette excise rates on smoking behavior, while the binary logistic regression test is to determine the effect of income on smoking behavior. Overall, respondents have filled out the questionnaire completely. Most respondents who smoke ≥ 15 cigarettes per day did not reduce the number of cigarettes they consumed per day, while only 11 people reduced it to 15 cigarettes. Then, respondents at income levels of 1,000,000-2,000,000 and 2,000,001-3,000,000, preferred not to reduce their cigarette consumption after the increase in cigarette excise rates. The increase in cigarette excise rates can reduce cigarette consumption in Malang society. For further research, it is expected to expand the scope of the research so that the results obtained can be more diverse.